Analyzing hydrological alteration and environmental flows in a highly anthropized agricultural river basin system using SWAT+, WEAP and IAHRIS - Sara Asadi; S. Jamshid Mousavi; Adrián López-Ballesteros; Javier Senent-Aparicio (Journal of Hydrology: Regional Studies, 2024)
Study region: Zarineh River Basin, a significant contributor to Urmia Lake inflow, Iran. Study focus: Employing SWAT+, WEAP, and IAHRIS, we assess environmental flow impacts on the Zarineh River Basin through two key aspects. Firstly, we evaluate the dam-induced alteration of the hydrological regime. Secondly, we explore future implications by prioritizing water allocation for environmental flows. Our approach involves developing, calibrating, and validating a SWAT+ hydrological model, analyzing hydrological alteration indicators using IAHRIS, and calculating environmental flows using the basic flow method in the SWAT+ post-processing tool. Using the WEAP water allocation model, three scenarios are assessed: 1) status quo, prioritizing drinking water and industry over agriculture; 2) environmental flows, prioritizing regulation compliance; 3) improved irrigation efficiency, facilitating a 10% increase while maintaining environmental flow prioritization.New hydrological insights for the region: The study reveals the altered flow regime’s failure to capture seasonal variations during dry years, particularly in winter and spring. Environmental and agricultural water demands compete, posing challenges to water management in the basin. Prioritizing environmental requirements increases reliability by 56% for environmental flows but decreases it by 11% for agriculture. Balancing environmental flows and agricultural water demands is crucial. A third scenario considers increased irrigation efficiency, requiring both decreased water allocation and enhanced efficiency. This research offers policymakers insights into formulating balanced environmental flow strategies, considering water demand reliability and basin hydrology.